An Increase of the Indonesian Throughflow by Internal Tidal Mixing in a High‐Resolution Quasi‐Global Ocean Simulation. Issue 16 (21st August 2018) - Sasaki, H.; Kida, S.; Furue, R.; Nonaka, M.; Masumoto, Y.
Abstract: The impact of internal tidal mixing on the volume transport of the Indonesian Throughflow (ITF) is examined by a comparison of high‐resolution quasi‐global ocean simulations with and without a tidal mixing scheme. The ITF transport is found to be increased in the presence of tidal mixing. This is because tidal mixing decreases the density within and below the lower thermocline and increases the buoyancy of the water column. As a result, the surface pressure and the sea surface height (SSH) are raised. The magnitude of the SSH increase is larger for the tropical Pacific Ocean than for the other basins, possibly because many islands exist in the tropical Pacific and tidal mixing is effective around their shallow and rough topographies. Since SSH increases more in the tropical Pacific than in the Indian Ocean, the pressure difference between the two basins is enhanced and thus the ITF transport is strengthened. Plain Language Summary: The Indonesian Throughflow (ITF) is an interbasin flow from the western Pacific Ocean to the Indian Ocean that passes through the Indonesian Seas and serves as the only branch that connects the two basins near the equator. The ITF plays a role in the climate variations in the Asia‐Pacific and Indian Ocean regions such as the El Niño, Indian Ocean Dipole, and Australian Summer Monsoon. High‐resolution oceanic simulations show that the ITF transport increases when the effect of internal tidal mixing is added to the model. The various steep slopes and shallow seamounts around the islands of the tropical Pacific Ocean work effectively as a region of enhanced vertical mixing and increases the buoyancy of the water column. An increase of sea surface height occurs over the equatorial Pacific Ocean, which enhances the pressure difference between the western Pacific Ocean and the Indian Ocean and, therefore, strengthens the ITF transport. Key Points: The Indonesian Throughflow transport increases when a tidal mixing scheme is used in a high‐resolution ocean general circulation model Tidal mixing decreases the density within and below the lower thermocline and raises the sea surface height A large increase of sea surface height occurs for the tropical Pacific and strengthens the Indonesian Throughflow transport